Algebraic manipulation is an art

Geometry Level 5

Let a 2 + b 2 = 1 { a }^{ 2 } + { b }^{ 2 } = 1 . such that a , b a,b \in \Re

If f ( a , b ) = β b α a f\left( a,b \right) = \cfrac { \beta - b }{ \alpha - a } for some fixed pair ( α , β ) (\alpha ,\beta ) such that α , β > 1 \alpha, \beta >1

Then maximum and minimum value of f ( a , b ) f\left(a, b \right) are γ \gamma and δ \delta respectively. And if

P = γ + δ + γ 2 + δ 2 P= \gamma + \delta + \sqrt { { \gamma }^{ 2 } + { \delta }^{ 2 } }

Then it can be expressed as:

P = K ( α β ) + L α 2 β 2 M ( α 2 1 ) ( β 2 1 ) α 2 1 P = \large \frac { K ( \alpha \beta ) + \sqrt { L { \alpha }^{ 2 } { \beta }^{ 2 } - M({ \alpha }^{ 2 }-1)({ \beta }^{ 2 }-1)} }{ { \alpha }^{ 2 }-1 }

Find the value of K + L + M K + L + M

This is part of set Click here

Details and Assumptions

  • Solve it geometrically!

  • K , L , M K , L , M are positive integers.


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Ariel Gershon
Dec 25, 2014

In this diagram, we see that for any point ( a , b ) (a,b) on the circle, we have a 2 + b 2 = 1 a^2 + b^2 = 1 and the slope of the line from ( a , b ) (a,b) to the point C C is exactly β b α a = f ( a , b ) \frac{\beta - b}{\alpha - a} = f(a,b) . Therefore, we need to find the points on the circle which maximize and minimize the slope. Say this happens at the points A A and B B respectively. Hence γ \gamma is the slope of B C BC and δ \delta is the slope of A C AC .

Now this means that A C AC and B C BC are tangent to the circle. Hence O A C = O B C = 9 0 o \angle OAC = \angle OBC = 90^{o} . We also know that O A = O B = 1 OA = OB = 1 and O C = α 2 + β 2 OC = \sqrt{\alpha^2 + \beta^2} . Furthermore let ε = O C A = O C B \varepsilon = \angle OCA = \angle OCB and θ \theta be the angle between O C OC and the x-axis.

Then we have γ = t a n ( θ ε ) \gamma = tan(\theta - \varepsilon) and δ = t a n ( θ + ε ) \delta = tan(\theta + \varepsilon) .

Using trigonometry, we find that ( 1 ) (1) t a n ( θ ) = β α tan(\theta) = \frac{\beta}{\alpha} and ( 2 ) (2) t a n ( ε ) = 1 α 2 + β 2 1 tan(\varepsilon) = \frac{1}{\sqrt{\alpha^2 + \beta^2 - 1}} .

The rest of my solution is algebra. It requires the following trigonometric identity: t a n ( θ + ε ) t a n ( θ ε ) = t a n 2 ( θ ) t a n 2 ( ε ) 1 t a n 2 ( θ ) t a n 2 ( ε ) . . . ( 3 ) tan(\theta + \varepsilon)tan(\theta - \varepsilon) = \frac{tan^2(\theta) - tan^2(\varepsilon)}{1 - tan^2(\theta)tan^2(\varepsilon)} . . . (3) Using ( 1 ) (1) , ( 2 ) (2) , ( 3 ) (3) and a bit of algebra, we get the following: γ × δ = β 2 1 α 2 1 . . . . ( 4 ) \gamma \times \delta = \frac{\beta^2 - 1}{\alpha^2 - 1} . . . . (4) Now we can use ( 1 ) (1) to get: t a n ( 2 θ ) = 2 α β α 2 β 2 . . . . ( 5 ) tan(2\theta) = \frac{2\alpha \beta}{\alpha^2 - \beta^2} . . . . (5) Now we also need the identity that t a n ( θ + ε ) + t a n ( θ ε ) = t a n ( 2 θ ) ( 1 t a n ( θ + ε ) t a n ( θ ε ) ) . . . ( 6 ) tan(\theta + \varepsilon) + tan(\theta - \varepsilon) = tan(2\theta)(1 - tan(\theta + \varepsilon)tan(\theta - \varepsilon)) . . . (6)

Now we can use ( 4 ) (4) , ( 5 ) (5) and ( 6 ) (6) to get: γ + δ = 2 α β α 2 1 . . . ( 7 ) \gamma + \delta = \frac{2\alpha \beta}{\alpha^2 - 1} . . .(7) Next using the fact that γ 2 + δ 2 = ( γ + δ ) 2 2 γ δ \gamma^2 + \delta^2 = (\gamma + \delta)^2 - 2\gamma\delta , we get γ 2 + δ 2 = 4 α 2 β 2 2 ( α 2 1 ) ( β 2 1 ) ( α 2 1 ) 2 . . . ( 8 ) \gamma^2 + \delta^2 = \frac{4\alpha^2 \beta^2 - 2(\alpha^2 - 1)(\beta^2 - 1)}{(\alpha^2 - 1)^2} . . .(8) Finally combine ( 7 ) (7) and ( 8 ) (8) : γ + δ + γ 2 + δ 2 = 2 α β + 4 α 2 β 2 2 ( α 2 1 ) ( β 2 1 ) α 2 1 \gamma + \delta + \sqrt{\gamma^2 + \delta^2} = \frac{2\alpha \beta + \sqrt{4\alpha^2 \beta^2 - 2(\alpha^2 - 1)(\beta^2 - 1)}}{\alpha^2 - 1} Hence K + L + M = 8 K+L+M = \boxed{8} .

Very Nicely Done !

Deepanshu Gupta - 6 years, 5 months ago
Deepanshu Gupta
Dec 6, 2014

See This Diagram image image

f ( a , b ) f(a,b) maximum and minimum values are geometrically means Slope of two tangents to the circle x 2 + y 2 = 1 { x }^{ 2 }\quad +\quad { y }^{ 2 }\quad =\quad 1 . from Point P( α \alpha , β \beta )

γ = m P B a n d δ = m P A \gamma \quad =\quad { m }_{ PB }\quad \quad and\quad \delta \quad =\quad { m }_{ PA }\quad .


Now Try to proceed further independently So that You Realise Beauty of this question :)

Did exactly same. wanted to give a solution but it was same as yours.

Gautam Sharma - 6 years, 3 months ago

i got \gamma as beta by alpha -1 and delta as beta by alpha +1 and i got k=2 but i'm not able to solve the sqaure root

Ashwin Gopal - 6 years, 6 months ago

Log in to reply

Actually You don't need to calculate γ \gamma and δ \delta individually for this question ! You may proceed in this way :

write equation of a line with slope "m" and pass through ( α \alpha , β \beta ) now drop perpendicular from (0,0) on this line , and make quadratic in "m" So note down m 1 + m 2 = ? m 1 m 2 = ? { m }_{ 1 }+{ m }_{ 2 }\quad =\quad ?\\ { m }_{ 1 }{ m }_{ 2 }\quad =\quad ? .

So P = m 1 + m 2 + ( m 1 + m 2 ) 2 4 m 1 m 2 = ? P\quad =\quad { m }_{ 1 }\quad +\quad { m }_{ 2 }\quad +\quad \sqrt { { ({ m }_{ 1 }+{ m }_{ 2 }) }^{ 2 }\quad -\quad 4{ m }_{ 1 }{ m }_{ 2 } } \quad =\quad ? .

Answers are : K=2 , L =4 , M=2

Deepanshu Gupta - 6 years, 6 months ago

Log in to reply

That will be ( m 1 + m 2 ) 2 2 m 1 m 2 \sqrt{(m_1+m_2)^2-2m_1m_2} in the last line. That's the easiest way, I think.

Soumava Pal - 5 years, 2 months ago

Beautiful. I just reshared it.

I did somewhat similar question in my coaching, the answer was same.

Ninad Akolekar - 6 years, 6 months ago
Oliver Piattella
Jan 12, 2016

Using polar coordinates a = cos ϕ a = \cos\phi and b = sin ϕ b = \sin\phi , function f f can be rewritten as: f = β sin ϕ α cos ϕ . f = \frac{\beta - \sin\phi}{\alpha - \cos\phi}\;. The extremum condition for f f , i.e. f = 0 f' = 0 , reads: β sin ϕ α cos ϕ = 1 tan ϕ . \frac{\beta - \sin\phi}{\alpha - \cos\phi} = -\frac{1}{\tan\phi}\;. Note that ϕ 0 \phi \neq 0 , since α > 1 \alpha > 1 by hypothesis. Notice also that the above equation can be interpreted as the orthogonality condition between the line joining ( a , b ) (a,b) to ( α , β ) (\alpha,\beta) and the radius. Therefore, the former is tangent to the circle. The above equation can be solved for the sine and the cosine, sin ϕ = β ± α α 2 + β 2 1 α 2 + β 2 , \sin\phi = \frac{\beta \pm \alpha\sqrt{\alpha^2 + \beta^2 - 1}}{\alpha^2 + \beta^2}\;, and cos ϕ = α β α 2 + β 2 1 α 2 + β 2 . \cos\phi = \frac{\alpha \mp \beta\sqrt{\alpha^2 + \beta^2 - 1}}{\alpha^2 + \beta^2}\;. Thus, substituting back into f f , we get: γ = β α 2 + β 2 1 α β + α α 2 + β 2 1 , \gamma = \frac{\beta\sqrt{\alpha^2 + \beta^2 - 1} - \alpha}{\beta + \alpha\sqrt{\alpha^2 + \beta^2 - 1}}\;, and δ = β α 2 + β 2 1 + α β α α 2 + β 2 1 . \delta = -\frac{\beta\sqrt{\alpha^2 + \beta^2 - 1} + \alpha}{\beta - \alpha\sqrt{\alpha^2 + \beta^2 - 1}}\;. Summation gives: γ + δ = 2 α β α 2 1 , \gamma + \delta = \frac{2\alpha\beta}{\alpha^2 - 1}\;, and multiplication gives: γ δ = β 2 1 α 2 1 . \gamma\delta = \frac{\beta^2 - 1}{\alpha^2 - 1}\;. Therefore, γ 2 + δ 2 = ( γ + δ ) 2 2 γ δ = 4 α 2 β 2 2 ( β 2 1 ) ( α 2 1 ) ( α 2 1 ) 2 . \gamma^2 + \delta^2 = (\gamma + \delta)^2 - 2\gamma\delta = \frac{4\alpha^2\beta^2 - 2(\beta^2-1)(\alpha^2 -1)}{(\alpha^2 - 1)^2}\;. Finally, we can read off from the expression for P P that K = 2 K = 2 , L = 4 L = 4 and M = 2 M = 2 , so that K + L + M = 8 . \boxed{K + L + M = 8}\;.

Moderator note:

Good approach. Going back and forth between the algebraic and the geometric interpretation, allows us to obtain information that could be translated into another language, with surprising results.

Suresh Yadav
Jul 29, 2017

Interesting question deepanshu bhaiya. Solved in the similar way as you did.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...